A construção de enunciados em uma escola do campo : perspectivas para uma linguagem de não violência em aulas de ciências - Silva, Isaque Nilson da (2022)
This research addresses the statements constructed in a rural school and their relationship with a non-violent language in science classes. The objective was to understand the relationships between student statements and non-violent language in science classes. For this, the theme of curricular violence and its link with the pedagogy of the oppressed were related to the concepts of Bakhtinian analysis, as foundations to reflect on the use of language in the classroom, considering the classroom as heterogeneous learning environments that transform at each meeting over the course of a school year or over a period of the subjects' school life. Dialogical relationships in the classroom were analyzed - from the extraverbal (social) and verbal (visual verb) dimensions of utterances. The reflections from this analysis indicated the existence of voices that produce situations of polyphony or monophony, present in the utterances issued in the school environment, more particularly in science teaching. As a main conclusion, it was identified that the language conceived in the classroom allowed the construction of statements for a non-violent language in science classes. At the end, the contributions to the reflections on the use of language and the perspectives for overcoming the manifestations of curricular violence against cultural identity, against individual identity and against the creative drive of students are discussed.